Development of Teaching Material for Narrative Writing Skills Using Brainwriting Models in Elementary Schools: Pengembangan Bahan Ajar Keterampilan Menulis Narasi Menggunakan Model Brainwriting di Sekolah Dasar - Lika apreasta; Andra Saputra (Journal of Vocational Education and Information Technology (JVEIT), 2020)
This study aims to describe the process of developing narrative writing teaching materials and producing narrative writing teaching materials using Brainwriting for teachers and fifth grade elementary school students that are valid, practical, and effective.Type of research and development. The development model used by the 4-D model. This research was conducted at SDN 18 Sitiung. The subject of the research was the fifth grade elementary school students. Validity test research data obtained through the validation sheet of teaching materials. Practicality data was collected through observation sheets of the implementation of the lesson plans, teacher and student response questionnaires, and observations of the use of teaching materials. Based on the validity test, obtained data that the average percentage of RPP obtained 90.2% of the expert validator and practitioner validator with a category that is very valid. The results of the average percentage of teaching materials obtained 92.43% of expert validators in the category of very valid, from the practitioner validator is 94.7% the category is very valid. The practicality test results of the implementation of the RPP with a percentage of 87.71% category is very practical. Teacher response assessment obtained 91.8% and assessment of student responses 89.2% very valid category.